PSYCHOMETRIC PROPERTIES OF THE SCALE: MY ONLINE TEACHER DURING A PANDEMIC: Received: 11th September, 2021; Revised: 11th December 2022, 24th January 2022, 05th February; 2022 Accepted: 09th February 2022 - Salubayba, Teodora Mabulay (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Surveys regarding digital online learning during the Covid-19 pandemic that proliferated on the internet utilized online instruments that are mostly open-ended questions and closed forms with insufficient reliability and validity evidence provided. Instrument technical adequacy is crucial in any research endeavor to warrant the trustworthiness of research conclusions. This study describes the development of an instrument to measure students’ observations of their online teachers during a pandemic. The 33-item instrument based on the responses to the open-ended online survey revealed acceptable internal consistency. The principal component analysis generated three subscales like personal traits and characteristics, classroom management skills and behavior, and communication and connectedness. Multiple comparisons discovered similarities and differences among the scores of the junior secondary, senior secondary, and college students across subscales. Subgroups like female and male students were compared that showed no significant difference in the subscales. Likewise, students in the public and private schools were significantly different in subscale 2 but not significantly different in the other subscales. The scale that was developed conjures the importance of research instruments’ technical adequacy to warrant appropriate and defensible conclusions about the phenomenon under investigation such as online teaching and learning during a pandemic.